Faktor-Faktor yang Berhubungan dengan Praktik Sanitasi dan Higiene Perorangan pada Siswa SMK - Putranto, Pradana Dian Juni; Rahardjo, Bambang Budi (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Sanitation and personal hygiene through the School Health Effort aims to improve students' ability to live a healthy life and health status, as well as create a healthy school environment in an effort to form healthy Indonesian people. The purpose of this study was to analyze the relationship between knowledge, attitudes, the role of parents and the role of the school with sanitation and personal hygiene practices. Methods: This type of research is explanatory research to explain the relationship between research variables through hypothesis testing. The research subjects were students of PP Assyyafiiyah Vocational School, Kendal Regency. Collecting data using a questionnaire. Sampling with simple random sampling technique. Data analysis used univariate and bivariate analysis of Product Moment correlation. Results: : The results showed that there was a relationship between knowledge and personal hygiene and sanitation practices of students (r = 0.566; p = 0.000), there was a relationship between attitudes and personal hygiene and sanitation practices of students (r = 0.823; p = 0.000), there was a relationship between parental roles and sanitation and personal hygiene practices of students (r = 0.754 ; p = 0.000), there is a relationship between the role of schools and sanitation and personal hygiene practices of students (r = 0.698; p value = 0.000). Conclusion: Knowledge, attitudes, parental roles and school roles have a significant relationship with individual sanitation and hygiene practices.